Enhanced NH3 Sensing Performance of Mo Cluster-MoS2 Nanocomposite Thin Films via the Sulfurization of Mo6 Cluster Iodides Precursor - Meiqi Zhang; Fabien Grasset; Yuji Masubuchi; Toshihiro Shimada; Thi Kim Ngan Nguyen; Noée Dumait; Adèle Renaud; Stéphane Cordier; David Berthebaud; Jean-François Halet; Tetsuo Uchikoshi (Nanomaterials, 2023)
The high-performance defect-rich MoS2 dominated by sulfur vacancies as well as Mo-rich environments have been extensively studied in many fields, such as nitrogen reduction reactions, hydrogen evolution reactions, as well as sensing devices for NH3, which are attributed to the under-coordinated Mo atoms playing a significant role as catalytic sites in the defect area. In this study, the Mo cluster-MoS2 composite was creatively synthesized through a one-step sulfurization process via H2/H2S gas flow. The Mo6 cluster iodides (MIs) coated on the fluorine-doped tin oxide (FTO) glass substrate via the electrophoretic deposition method (i.e., MI@FTO) were used as a precursor to form a thin-film nanocomposite. Investigations into the structure, reaction mechanism, and NH3 gas sensing performance were carried out in detail. The results indicated that during the gas flowing, the decomposed Mo6 cluster iodides played the role of template and precursor, forming complicated Mo cluster compounds and eventually producing MoS2. These Mo cluster-MoS2 thin-film nanocomposites were fabricated and applied as gas sensors for the first time. It turns out that after the sulfurization process, the response of MI@FTO for NH3 gas increased three times while showing conversion from p-type to n-type semiconductor, which enhances their possibilities for future device applications.